1995
DOI: 10.1093/ajcp/103.6.696
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Perineurioma:A Clonal Neoplasm Associated With Abnormalities of Chromosome 22

Abstract: The nature of perineurioma, variably termed "localized hypertrophic neuropathy," "intraneural neurofibroma," and "hypertrophic interstitial neuritis" has long been an issue of contention. Most authors consider it a neoplasm, but some a reactive process. Eight clinically and morphologically typical perineuriomas were studied by histologic, immunohistochemical and ultrastructural methods. One perineurioma was subject to tissue culture and cytogenetic study and another to fluorescence in situ hybridization (FISH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 0 publications
5
167
1
2
Order By: Relevance
“…In 1995, Emory et al [9] demonstrated the clonal nature of the intraneural perineurioma and its association with abnormalities of chromosome 22. Giannini et al [8] also showed a deletion of part or all of chromosome 22 in extraneural perineuriomas and supported the view that both types of perineuriomas are neoplasms of perineurial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, Emory et al [9] demonstrated the clonal nature of the intraneural perineurioma and its association with abnormalities of chromosome 22. Giannini et al [8] also showed a deletion of part or all of chromosome 22 in extraneural perineuriomas and supported the view that both types of perineuriomas are neoplasms of perineurial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, three other useful but nonspecific stains cited in the literature that can aid in diagnosis are Glut-1, claudin-1, and collagen type-IV [1,2,4,7]. Perineuriomas are ultrastructurally and immunohistochemically similar to normal perineurial cells, but are clonal, frequently reported to demonstrate a deletion of the region of chromosome 22 where the tumor suppressor gene NF2 resides [1,2,5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, a predilection for the upper extremity was reported [6]; however, research has found a nearly equal incidence of upper and lower extremity involvement [12][13][14]. The definitive cause of these tumors is still being investigated [5,10].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…8 Tipicamente, uma proliferação de células perineurais de formato fusiforme ocorre no corpo de um tronco nervoso e se dispõe em redemoinhos concên-tricos ao redor de axônios e células de Schwann preexistentes e comprimidos. Esse padrão é observado mais facilmente nos cortes transversais.…”
Section: Perineurioma Intraneural (Pi)unclassified